Jurisdictional Challenges in Cryptocurrency Disputes: Navigating the Legal Maze of a Borderless Technology - Damap, Nanjwan Yale Damap; Maza, Kangdim Dingji Maza (African Journal of Stability and Development (AJSD), 2025)
The rise of cryptocurrencies and blockchain technology has introduced complex legal challenges, particularly concerning jurisdiction in dispute resolution. Traditional legal frameworks rely on geographic boundaries and centralised authority, yet cryptocurrencies operate on decentralised, borderless networks. This article examines the jurisdictional issues that arise in cryptocurrency disputes, including the challenges of determining the applicable law, identifying the responsible parties, and enforcing legal decisions across multiple jurisdictions. By analysing key legal precedents and international regulatory approaches, the study highlights the limitations of existing legal principles in addressing crypto-related conflicts. Further analysis of emerging solutions, such as smart contract jurisdiction clauses, decentralised arbitration, and proposals for harmonised international regulatory frameworks, was also studied in the article. Findings of the article suggest the need for innovative legal mechanisms that balance regulatory oversight with the decentralised nature of blockchain technology.